1991
DOI: 10.1159/000138807
|View full text |Cite
|
Sign up to set email alerts
|

Additional Antilipoperoxidant Activities of Alpha-Tocopherol and Ascorbic Acid on Membrane-Like Systems Are Potentiated by Rutin

Abstract: The effects of α-tocopherol, ascorbic acid and rutin on peroxidative processes were studied in xanthine-xanthine oxidase system, linoleic acid ufasomes and human erythrocyte membranes. In these three systems, tested compounds scavenge superoxide anion radicals or inhibit lipid peroxidation in a concentration-dependent manner, and it was shown that rutin was the most potent radical scavenger, followed by ascorbic acid and α-tocopherol. An important antilipoperoxidant activity was observed when these compounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Ascorbate was found to be stimulatory, rather than inhibitory, which could be explained by the observation that under certain conditions ascorbate functions as a pro-oxidant, rather than an antioxidant, possibly due to the ability of ascorbic acid to release transitional metal ions from protein complexes leading to the generation of free radicals (71)(72)(73)(74)(75)(76)(77). Ascorbic acid has been shown to protect a-tcp from oxidation and in doing so enhance the latter's antioxidant activity (78)(79)(80). In our studies the addition of ascorbate plus a-tcp led to no net effect on agonistinduced monocyte adhesion, which suggests the possibility that the a-tcp reduced the enhancement in IL-1-induced adhesion caused by ascorbate alone.…”
Section: Effect Of A-tcp On Ec Expression Of E-selectin It Has Beenmentioning
confidence: 99%
“…Ascorbate was found to be stimulatory, rather than inhibitory, which could be explained by the observation that under certain conditions ascorbate functions as a pro-oxidant, rather than an antioxidant, possibly due to the ability of ascorbic acid to release transitional metal ions from protein complexes leading to the generation of free radicals (71)(72)(73)(74)(75)(76)(77). Ascorbic acid has been shown to protect a-tcp from oxidation and in doing so enhance the latter's antioxidant activity (78)(79)(80). In our studies the addition of ascorbate plus a-tcp led to no net effect on agonistinduced monocyte adhesion, which suggests the possibility that the a-tcp reduced the enhancement in IL-1-induced adhesion caused by ascorbate alone.…”
Section: Effect Of A-tcp On Ec Expression Of E-selectin It Has Beenmentioning
confidence: 99%
“…30 Rutin is an important antilipoperoxidant agent and has been found to be a strong scavenger of superoxide and hydroxyl radicals. 31,32 Furthermore, Robak and Gryglewski 33 have shown that rutin is a scavenger of the superoxide dismutase-sensitive free radicals. It has been reported that flavonoids inhibit xanthine-oxidase, cytochrome P450-dependent estrogen synthase, lipoxygenase and some other enzymes.…”
mentioning
confidence: 99%
“…Although flavonoids, which are widely distributed in the plant kingdom, have been recognized to show various biological activities, the effects of specific iNOS inhibition of rutin have not been discussed extensively. 31,33,34 Thus, we designed the present study to determine whether rutin can inhibit iNOS activity and reduce 3-NT formation in the kidneys of rats during I/R. We examined plasma nitrite/nitrate and cGMP concentrations in all experimental groups.…”
mentioning
confidence: 99%
“…This result was supported in the presented study where the GSH level and the GPx, CAT and SOD activities of the lung tissue in the OA group were significantly lower compared to those in the control and rutin 150 mg groups. It is indicated that rutin is an antilipoperoxidant agent [35] and a strong free radical scavenging [36] . Rutin has been indicated to increase the levels of SOD and CAT in rats with cerebral ischemia-reperfusion [37] .…”
Section: Discussionmentioning
confidence: 99%